Sarah : the life of Sarah Bernhardt - Gottlieb, Robert, 1931-2023 (Jewish lives (New Haven, Conn.), 2010)
Everything about Sarah Bernhardt is fascinating, from her obscure birth to her glorious career--redefining the very nature of her art--to her amazing (and highly public) romantic life, to her indomitable spirit. Well into her seventies, after the amputation of her leg, she was performing under bombardment for soldiers during World War I and toured America for the ninth time. Though the Bernhardt literature is vast, this is the first English-language biography to appear in decades, tracking the trajectory through which an illegitimate--and scandalous--daughter of a Jewish courtesan transformed herself into the most famous actress who ever lived, and into a national icon, a symbol of France.--From publisher description.